The Price Effect of Drug Price Ceilings: Intended and Unintended Consequences - Li, Jun; Wu, Di (Andrew) (Management Science, 2022)
Policy makers in many developing countries use maximum price or markup policies to control pharmaceutical costs, which represent 20%–60% of their overall healthcare expenditure. We study the price effect of price ceiling policies by exploiting a major policy shift in China: the elimination of longstanding ceilings on retail drug prices. We collect weekly price and characteristics data on more than 4,500 drug stock keeping units (SKUs) from a leading pharmacy chain. By comparing the rate of discontinuous price jumps across drugs with and without price ceilings during the years before and after the policy change, we find that while price ceilings are effective in containing the prices of some drugs, they can lead to higher prices for others, particularly if the ceilings are set at the national level irrespective of local economic conditions. About 5% of nationally controlled drugs (or more than 125 drugs) had inflated prices because of price ceilings, with an average price inflation of 10%. We attribute this perverse price effect to focal point pricing and asymmetric information about production costs. Further supporting this view, we find the perverse price effect most prominent in lower-income regions where the centrally set price ceilings are arbitrarily high considering their poorer economic conditions. Moreover, drugs with highly concentrated production and less elastic demand face heightened risks of inflated prices under price ceilings. Finally, based on a sample of drugs with available price ceiling data, we find that drugs with manufacturer-specific ceilings are 100% more likely to be priced at or near their ceilings and 70% more likely to experience price drops once the ceilings are removed compared with other drugs with regular ceilings. Overall, this paper documents the unintended perverse effect of price ceilings in pharmaceutical markets and sheds lights on the ongoing debate of drug price regulation. This paper was accepted by Stefan Scholtes, healthcare management.